Dynamics of Change in Spatial Dependencies in Blood Donation System in Poland - Ojrzyńska, Anna; Twaróg, Sebastian (Comparative Economic Research. Central and Eastern Europe, 2013)
Blood donation allows to obtain blood and its components from healthy people in a bid to help treatment of anonymous individuals, relying on timely and sufficient supplies of matching blood. Being a social initiative, it depends on multiple factors. Those factors are possible to be shaped and are subject to research. This paper aims to present the dynamics of change in spatial dependencies determining development of blood donation in Poland from 2005 to 2010. Spatial analysis of data enables identification of similarities and differences between voivodeships in a given period. Testing of hypothesis concerning spatial autocorrelation was carried out using tools of spatial statistics. This paper’s subject matter concentrates on pointing towards the direction and extent of changes illustrated with an example of analysis investigating the number of blood donations per hospital bed in wards with high demand on blood and its components. The number of blood donors per 1000 residents in 18 – 65 age was also analysed.